Analytical description of intelligent controlled U-free bending process in wide plate. (May 2015) - Su, C.; Zhao, J.; Guo, S.
<x content-type="archive" xml:space="preserve">Abstract</x> Based on the flexure theory of plate, and the assumption of plane deformation, an analytic model of U-free bending theory is proposed, which considered the hardening, anisotropy and elastic deformation of the material. Using this model, the change rules of bending force with bending stroke and the formula of target angularity are obtained, and the various factors affecting bending force and rebound are analysed. Furthermore, the results of theoretical calculations, experiments and simulations are compared, which provide the theoretical basis for identifying the parameters of the intelligent controlled free U-bending in wide plate, as well as determine variables of the input and output layer of the predicted model.